Cognitive linguistics as a part of cognitive science - Makhmudova, Makhmudakhon (The Lingua Spectrum, 2025)
This study explores the role of cognitive linguistics within the wider scope of cognitive science. It examines how this discipline developed in history through the works of Humboldt, Potebnya, Baudouin de Courtenay, Vygotsky, and Luria, to its recognition as an interdisciplinary field of study. This article also highlights the theoretical frameworks proposed by Lakoff and Johnson, Langacker, Fillmore, and Goldberg, which shaped the modern trajectory of the discipline. The article also traces the methodology of cognitive research, the outcomes of linguistic analysis, and the practical applications of cognitive linguistics in education, artificial intelligence, neurorehabilitation, and cross-cultural studies.